Symptomatic Relief in Sickle Cell Disease Patients by Homeopathy Medicines (Advancements in Homeopathic Research, 2023)
Sickle cell disease (SCD) is a hereditary blood  syndrome that affects the shape and passage of red  blood cells (RBCs) in blood vessels, which leads  to several medical complications. Normal red  blood cells are round or oval. In people with sickle  cell disease, the haemoglobin which is a substance  present in red blood cells becomes defective and in  turn leads to the change in shape of the red blood  cells. Red blood cell becomes like sickles or crescent  moons in the persons suffering from sickle cell  disease. These inflexible, sticky cells may get trapped  in small blood vessels, which in turns reduces or  blocks blood flow and oxygen to different parts of the  body. As such there is no cure for sickle cell disease  but homeopathic Medicines can relieve pain and help  prevent complications associated with the Sickle cell  disease (SCD). In this paper we have presented our  research on symptomatic relief in sickle cell disease  patients by homeopathy.
Keywords: Sickle Cell Disease (SCD); Haemoglobin; Homeopathy; Blood Transfusion Anemia etc